2005
DOI: 10.1162/15353500200505145
|View full text |Cite
|
Sign up to set email alerts
|

Cellular MR Imaging

Abstract: Cellular MR imaging is a young field that aims to visualize targeted cells in living organisms. In order to provide a different signal intensity of the targeted cell, they are either labeled with MR contrast agents in vivo or prelabeled in vitro. Either (ultrasmall) superparamagnetic iron oxide [(U)SPIO] particles or (polymeric) paramagnetic chelates can be used for this purpose. For in vivo cellular labeling, Gd3+- and Mn2+-chelates have mainly been used for targeted hepatobiliary imaging, and (U)SPIO-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
273
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(274 citation statements)
references
References 173 publications
(236 reference statements)
1
273
0
Order By: Relevance
“…Ultrasmall (20-40 nm) SPIO (USPIO) primarily accumulate in the lymph nodes and bone marrow, and are useful in identifying metastatic lymph nodes. Such particles may be applied to track stem cells transplanted into organs or to demonstrate macrophage activity within atherosclerotic plaque [9], and are also a suitable tool to label molecular probes targeting specific tumour-associated markers. Recently, arginine-glycine-aspartic acid USPIO (RGD-USPIO) have been used for in vivo imaging of angiogenesis in xenografts.…”
Section: Contrast Mediamentioning
confidence: 99%
“…Ultrasmall (20-40 nm) SPIO (USPIO) primarily accumulate in the lymph nodes and bone marrow, and are useful in identifying metastatic lymph nodes. Such particles may be applied to track stem cells transplanted into organs or to demonstrate macrophage activity within atherosclerotic plaque [9], and are also a suitable tool to label molecular probes targeting specific tumour-associated markers. Recently, arginine-glycine-aspartic acid USPIO (RGD-USPIO) have been used for in vivo imaging of angiogenesis in xenografts.…”
Section: Contrast Mediamentioning
confidence: 99%
“…Several techniques for in vivo cellular imaging are now available that allow the characterization of transplanted cells in the living organism, including magnetic resonance imaging (MRI), 23 bioluminescence, 24 positron emission tomography 25 and multiple photon microscopy. 26 All of these imaging methods, based on different principles, provide distinctive, usually complementary information.…”
Section: Cellular Imagingmentioning
confidence: 99%
“…by which stem cell therapy results in therapeutic benefit This has led to a vast amount of studies using a variety been hardly addressed so far. In this study these issues were addressed using bone marrow-derived mesenchyof iron oxide particles and labeling procedures (6,11,21,35,37,46,49,51,52,58,60,61). These studies showed that for mal stem cells.…”
Section: Introductionmentioning
confidence: 99%